Fresno County Women Lawyers Dinner with Patricia Shiu and Nancy DeStefanis - Watkins, Howard::::::::: (1987)
California Women Lawyers President Patricia Shiu congratulating 1987 Fresno County Women Lawyers President Karen Kern